Integrated asset management system for performance-based road maintenance contracts - Abu-Samra, Soliman (AUC Knowledge Fountain, 2014)
Performance-based maintenance contracts (PBMC) for highways are increasingly becoming an attractive mechanism for transferring activities traditionally undertaken by the public sector to private entities. Increased financial pressures on governments, demands for improved service levels by highway users, and the operational efficiencies offered by the private sector, all create a strong business case for PBMC. In order to enable government road agencies and private sector investors to engage in the use of PBMC, there is a need for quantitative tools that allow both entities to 1) Properly structure the PBMC in terms of risk allocation, 2) Develop appropriate levels for service level penalties and incentives in the contract, 3) Determine appropriate targets for highway level of service, and 4) Determine the most cost-effective set of road maintenance and rehabilitation (M&R) activities to be undertaken throughout the duration of the contract. This research developed a GIS-based Integrated Highway Asset Management System (IHAMS), which extends typical functionality of traditional pavement management systems to cover specific contractual requirements of PBMC. The system allows the analysis of both network-level and project-level asset management decisions. Defect-specific pavement deterioration models are developed using multivariate regression. Stochastic network-level deterioration models are developed using markov chains. Life cycle costing models are developed to cover specific financial obligations in PBMC like penalties and incentives, in addition to traditional M&R expenditure. A GA-based optimization modules is used to trade-off various decision scenarios that are beneficial to both road maintenance contracts and road agencies. A case study for the Cairo-Ismalliyah desert highway is used to demonstrate the capability of the system.